Energy substrate metabolism during dual work rate exercise: Effects of order - Egan, D.; Head, T. (Journal of Sports Sciences, 1999)
Changes in workload are evident during many physical activities. The aim of this study was to assess total substrate metabolism when the temporal placement of a period of higher-intensity work (75% VO2max) was varied within a low-intensity exercise session (50% VO2max). One experimental trial (higher intensity first) comprised 5 min low-intensity work, followed by 15 min high-intensity work, followed by 40 min low-intensity work. The other trial (low intensity first) comprised 40 min low-intensity work, followed by 15 min high-intensity work, followed by 5 min low-intensity work. The trials were designed to achieve an identical total energy expenditure. Energy expenditure, fat and carbohydrate utilization were estimated by expired gas analysis and compared between conditions. Mean total energy expenditure during the higher-intensity phase was 1076 kJ and 1128 kJ in the high-intensity first and low-intensity first trials respectively (t6= -3.76, P = 0.0047). Mean total energy expenditure for the whole trial was 3356 kJ and 3452 kJ in the high-intensity first and low-intensity first trials respectively (t6 = -3.48, P = 0.0065). Mean whole-trial fat utilization was 1753 kJ and 1857 kJ in the high-intensity first and low-intensity first trials respectively (t6 = -0.76, P = 0.24). Our findings suggest that changing the temporal placement of higher-intensity work within a low-intensity exercise session has a significant effect on total energy expenditure but not on the rate of fat oxidation.